Detection of new Delhi Metallo-β-lactamase-1 (NDM-1) gene from multidrug-resistant pseudomonas aeruginosa isolated from Dhaka Medical College Hospital - Amin, Md. Ruhul (BRAC, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.